Multi-Modal Learning Strategies and EFL Speaking Accuracy: Insights from a University Setting - Sumirna; Said, Saiful; Bakri, Rina; Nurfaisah Sahib (Eduvelop: Journal of English Education and Development, 2026)
This study investigates the effectiveness of the SAVI (Somatic, Auditory, Visual, Intellectual) method in enhancing the speaking ability of third-semester EFL students at the Muslim University of Indonesia. The research employed a pre-experimental design, utilizing pre-test and post-test assessments to evaluate changes in students’ speaking performance. Thirty-two students participated in the study, with speaking accuracy measured in terms of pronunciation, grammar, vocabulary, and fluency. The findings revealed significant improvements in students’ speaking ability after the SAVI intervention. The mean pre-test score of 2.59 increased to 5.25 in the post-test, and statistical analysis confirmed a significant difference between the two assessments. Students exhibited enhanced articulation, grammatical accuracy, and lexical richness, alongside greater confidence and willingness to participate in oral activities. These results indicate that multi-sensory learning strategies can foster holistic development and strengthen communicative competence, surpassing traditional lecture-based approaches in promoting effective language use. The study highlights the practical implications of integrating SAVI methods into EFL instruction, emphasizing the value of active engagement, real-time feedback, and interactive classroom practices. The findings suggest that educators can achieve measurable improvements in speaking proficiency by employing sensory-based pedagogical interventions. Additionally, the research provides insights for curriculum designers and teacher training programs, advocating for flexible, learner-centered approaches that align with modern communicative language teaching principles.